It’s a Process: Reactions to HIV Diagnosis and Engagement in HIV Care among High-Risk Heterosexuals - Kutnick, Alexandra H.; Gwadz, Marya Viorst; Cleland, Charles M.; Leonard, Noelle R.; Freeman, Robert; Ritchie, Amanda S.; McCright-Gill, Talaya; Ha, Kathy; Martinez, Belkis Y.; , The BCAP Collaborative Research Team; Banfield, Angela; Belkin, Mindy; et al. (Frontiers in Public Health, 2017)
After HIV diagnosis, heterosexuals in high-poverty urban areas evidence delays in linkage to care and antiretroviral therapy (ART) initiation compared to other groups. Yet barriers to/facilitators of HIV care among these high-risk heterosexuals are under-studied. Under the theory of triadic influence, putative barriers to HIV care engagement include individual/attitudinal-level (e.g., fear, medical distrust), social-level (e.g., stigma), and structural-level influences (e.g. poor access). Participants were African American/Black and Hispanic adults found newly diagnosed with HIV (N=25) as part of a community-based HIV testing study with heterosexuals in a high-poverty, high-HIV-incidence urban area. A sequential explanatory mixed-methods design was used. We described linkage to HIV care and clinical outcomes (CD4 counts, viral load levels) over one year, and then addressed qualitative research questions about the experience of receiving a new HIV diagnosis, its effects on timely engagement in HIV care, and other barriers and facilitators. Participants were assessed five times, receiving a structured interview battery, laboratory tests, data extraction from the medical record, a post-test counseling session, and in-person/phone contacts to foster linkage to care. Participants were randomly selected for qualitative interviews (N=15/25) that were recorded and transcribed, then analyzed using systematic content analysis. Participants were 50 years old, on average (SD=7.2 years), mostly male (80%), primarily African American/Black (88%), and low socioeconomic status. At the first follow-up, rates of engagement in care were high (78%), but viral suppression was modest (39%). Rates improved by the final follow-up (96% engaged, 62% virally suppressed). Two-thirds (69%) were adequately retained in care over one year. Qualitative results revealed multi-faceted responses to receiving an HIV diagnosis. Problems accepting and internalizing one’s HIV status were common. Reaching acceptance of one’s HIV-infected status was frequently a protracted and circuitous process, but acceptance is vital for engagement in HIV care. Fear of stigma and loss of important relationships were potent barriers to acceptance. Thus, partially as a result of difficulties accepting HIV status, delays in achieving an undetectable viral load are common in this population, with serious potential negative consequences for individual and public health. Interventions to foster acceptance of HIV status are needed.